Enzyme induced calcium carbonate precipitation and its engineering application: A systematic review and meta-analysis. (15th November 2021) - Ahenkorah, Isaac; Rahman, Md Mizanur; Karim, Md Rajibul; Beecham, Simon
Graphical abstract: Highlights: Enzyme induced calcium carbonate precipitation (EICP) is a sustainable method of soil improvement. The sources of urease enzymes used in the EICP process are compiled. Factors affecting the EICP process are discussed. Mechanical and microstructural response for EICP-treated soils are evaluated. Potential engineering applications of EICP are discussed. Abstract: Microbially induced calcium carbonate precipitation (MICP) and enzyme induced calcium carbonate precipitation (EICP) are the two most widely known bio-cementation techniques, particularly the former. EICP offers several benefits over MICP such as the smaller size of the urease enzyme making it applicable to a wider range of soils and simpler application processes. This review critically examines existing research on the EICP technique and provides an original meta -analysis of the available data. It is understood that factors such as the source and activity of the urease enzyme, the concentration of the chemical constituents (urea, calcium chloride and urease enzyme), the treatment approach used and the morphology of the precipitated calcium carbonate (CaCO3 ) may all affect the performance of the EICP treated material. Consequently, various enhancing additives including magnesium chloride (MgCl2 ), magnesium sulfate (MgSO4 ), zeolite, dried non-fat milk, xanthan gum, sisal fibre and cabbage juice have been utilised in recent studies to improve on the effectiveness of the EICP process. In this review, engineering parameters such as the unconfined compressive strength are correlated to the CaCO3 content ( CC ) and soil uniformity coefficient (Cus ) for EICP treated soils using compiled data from previous literature. However, the strength of EICP-treated soil may also depend on the particular polymorph, contact location and distribution of precipitated CaCO3 as well as the soil particle size and shape.